Analisis Pengaruh Online Customer Review Di Youtube, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Smartphone Samsung (Studi Kasus Mahasiswa Fakultas Ekonomi & Bisnis Universitas Islam Malang Program studi Manajemen angkatan 2019) - Rinaldi, Pipit Alhasan; Rachma, N; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of Yotube Online customer Reviews (X1), Product Quality (X2), and Price (X3) on Samsung Smartphone Purchase Decisions (Y). This type of research is quantitative research. By taking samples from students from the Faculty of Economics, Islamic University of Malang, class of 2019, as many as 100 people had purchased Samsung brand smartphones as research subjects. Sampling used a formula technique from Naresh K Malhotra, and data collection was carried out using a survey method by distributing questionnaires. Data were processed using the SPSS application by carrying out instrument tests, normality tests, classical assumption tests, multiple regression tests, hypothesis tests and coefficient of determination tests. Based on the test results in this research, it shows that the variables Online Reviews on YouTube (X1), product quality (X2), and Price (X3) simultaneously have a positive and significant effect on the Purchase Decision (Y) of Samsung Smartphones. Meanwhile, partially the variables Online Reviews on YouTube (X1), product quality (X2), and Price (X3) have a positive and significant effect on the Purchase Decision (Y) of Samsung Smartphones. Keywords: Online Reviews On Youtube, Product Quality, Price, Purchasing Decisions